2014
DOI: 10.1080/09712119.2014.928630
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fermentation products ofCordyceps militarison growth performance and bone mineralization of broiler chicks

Abstract: The present study aimed to evaluate the effects of fermentation products of Cordyceps militaris (FPCM) on growth performance and tibia mineralization of broiler chicks. A total of 240 one-day-old female Ross 308 broilers were allotted into four treatments with six cages of 10 chicks each. Four diets were the control diet supplemented with 0, 1, 2 and 4 g/kg of FPCM, respectively. Compared with the control, supplementation of 1 g/kg FPCM improved body weight gain of broilers from 22 to 42 days of age and from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
7
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
6
7
1
1
Order By: Relevance
“…Notably, the inclusion of SM improved the growth performance of weaning pigs. This improvement agrees with previous observations showing that the addition of 1, 2, and 10 g/kg SM significantly improved the zootechnical performance of broiler chickens, growing pigs, and Nile tilapia, respectively [ 23 , 24 , 26 ]. This positive effect may be caused by the weaning pigs being able to uptake nutrients more efficiently and maintain their health status, resulting in better growth performance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, the inclusion of SM improved the growth performance of weaning pigs. This improvement agrees with previous observations showing that the addition of 1, 2, and 10 g/kg SM significantly improved the zootechnical performance of broiler chickens, growing pigs, and Nile tilapia, respectively [ 23 , 24 , 26 ]. This positive effect may be caused by the weaning pigs being able to uptake nutrients more efficiently and maintain their health status, resulting in better growth performance.…”
Section: Discussionsupporting
confidence: 92%
“…Spent mushroom (SM) from C. militaris contains various bioactive compounds such as gamma-oryzanol, cordycepin, adenosine, D-mannitol, and polysaccharides [ 21 , 22 , 23 ]. The use of C. militaris significantly improved growth performance and immunity [ 24 , 25 ], in agreement with a previous study in which Nile tilapia were fed 10 g/kg SM [ 26 ]. The supplementation of 2 g/kg SM in the diet has recently been reported to stimulate immunoglobulin secretion and antioxidant activity in growing pigs [ 22 ].…”
Section: Introductionsupporting
confidence: 89%
“…Furthermore, many studies have reported that Cordyceps substances and active ingredients have the ability to improve growth performance and antioxidant function. The improvement of growth performance in broiler chicks (18) and laying hens (19) after feeding with fermentation products and the by-product of Cordyceps militaris, and the enhancement of BW and feed conversion rate of white shrimp (20) after supplementing with Cordyceps polysaccharides suggest that Cordyceps substances and active ingredients are effective in applications for animal husbandry. Additionally, our previous study showed that ATC supplementations accelerated the BW gain of calves, increased the BW and feed efficiency, and improved antioxidant and immune functions (7), which are results similar to those of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is marketable in western countries as an over-the-counter medicine. Recently, Hana et al (2014) indicated that supplementation of 0.1% fermentation products of Cordyceps militaris (FPCM) could increase the body weight gain of broilers from 22 to 42 days of age. Hence, the addition of 0.2% FPCM significantly increased the tibia calcium content at 21 and 42 days of chicken broilers; therefore, the authors suggested that FPCM had positive effects on the growth performance of broilers.…”
Section: Introductionmentioning
confidence: 99%